Os gastos públicos em agricultura no Espírito Santo: uma análise acerca do Plano Estratégico de Desenvolvimento da Agricultura Capixaba (PEDEAC) - Covre, Julyana (2013)
Since 2003, the state of Espírito Santo has undergone several changes institutional policies, when there were changes in agricultural policy guidelines state, through the Strategic Plan for Agriculture Capixaba (PEDEAG). The study aims to examine whether, due to the implementation of PEDEAG, a change in the spending pattern of the State and assess the relationship between the evolution of public spending in the state of Espírito Santo and its impacts on agricultural production growth.To achieve this goal, we propose a descriptive analysis of public spending on agriculture and estimation of agricultural production function, in two approaches: using as dependent variable agricultural production of the municipalities and counties of agricultural GDP and as explanatory variables, the land factor , human capital, use of fertilizers, technical guidance, number of tractors and municipal public spending. As a result, it was observed that the State expenditure followed guidelines PEDEAG. And that in aggregate public spending on agriculture municipalities followed the behavior of state spending on agriculture. The production functions estimated proved the positive impact of spending on agriculture in both output value of agriculture, as in agricultural GDP, however the technical guidance presented negative, contrary to expectations. It was also found that the deployment of the poles of fruit, except the poles mango and guava, positively impacted the agricultural GDP.